2009
DOI: 10.1007/s00467-008-1045-1
|View full text |Cite
|
Sign up to set email alerts
|

Urinary transforming growth factor beta1 in children and adolescents with congenital solitary kidney

Abstract: The aim of the study was to assess urinary transforming growth factor beta1 (TGF beta1) level in children and adolescents with congenital solitary kidney (CSK), depending on estimated glomerular filtration rate (eGFR) and compensatory overgrowth of the kidney. The study group (I) consisted of 65 children and young adults, 0.5-22 years of age (median 10.0 years) with CSK and no other urinary defects. The control group (C) contained 44 healthy children and adolescents, 0.25-21 years old (median 10.3 years). We u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 58 publications
(62 reference statements)
2
8
0
Order By: Relevance
“…[24]. The TGFβ-1 urinary levels in our series, both in the controls and patients, were also similar to the findings of Wasilewska et al [24].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…[24]. The TGFβ-1 urinary levels in our series, both in the controls and patients, were also similar to the findings of Wasilewska et al [24].…”
Section: Discussionsupporting
confidence: 80%
“…[24]. The TGFβ-1 urinary levels in our series, both in the controls and patients, were also similar to the findings of Wasilewska et al [24]. In summary, we studied the usefulness of the urinary excretion of TGFβ-1 as an early and noninvasive biomarker of renal hemodynamic changes due to a reduction in the number of functioning nephrons in D+HUS patients.…”
Section: Discussionsupporting
confidence: 69%
“…It has been speculated that the production of active fibrotic cytokines recognized in several kidney diseases as markers of disease activity and histopathological deterioration, might also be increased in the set of obesity (23). Such substances were shown to be increased in children with congenital single kidney in comparison with controls, even in early phases of hyperfiltration when proteinuria and renal insufficiency are still absent (24). Since kidney diseases with reduced renal mass are believed to mimic what happens in obesity, representing the clinical translation of the experimental hyperfiltration models (25), the increased levels of these substances, promoted in the proinflammatory and pro-oxidant setting of obesity, might partially explain the kidney impairment observed.…”
Section: Articlesmentioning
confidence: 87%
“…Wasilewska et al [9] reported increased levels of serum uric acid in children with congenital solitary kidney. In adults, hyperuricemia is an independent risk factor for new-onset chronic kidney disease (CKD) [9, 10], and has been suggested to be an early indicator of renal dysfunction [11].…”
Section: Discussionmentioning
confidence: 99%
“…Wasilewska et al [9] reported increased levels of serum uric acid in children with congenital solitary kidney. In adults, hyperuricemia is an independent risk factor for new-onset chronic kidney disease (CKD) [9, 10], and has been suggested to be an early indicator of renal dysfunction [11]. While uric acid is known to be an early marker for developing hypertension [12], it has not been paid much attention in many previous studies on solitary functioning kidney in children.…”
Section: Discussionmentioning
confidence: 99%